(untitled) (Journal of Health, Population and Nutrition, 2011)
In Nepal, most births take place at home, and many, particularly in rural areas, are not attended by a skilled birth attendant. The main objectives of the study were to assess the use of skilled delivery care and barriers to access such care in a rural community and to assess health problems during delivery and seeking care. This cross-sectional study was carried out in two Village Development Committees in Nepal in 2006. In total, 150 women who had a live birth in the 24 months preceding the survey were interviewed using a structured questionnaire. The sample population included married women aged 15-49 years. Forty-six (31%) women delivered their babies at hospital, and 104 (69%) delivered at home. The cost of delivery at hospital was significantly (p<0.001) higher than that of a delivery at home. Results of univariate analysis showed that women from Brahmin-Chhetri ethnicity, women with higher education or who were more skilled, whose husbands had higher education and more skilled jobs, had first or second childbirth, and having adverse previous obstetric history were associated with institutional delivery while women with higher education and having an adverse history of pregnancy outcome predicted the uptake of skilled delivery care in Nepal. The main perceived problems to access skilled delivery care were: distance to hospital, lack of transportation, lack of awareness on delivery care, and cost. The main reasons for seeking intrapartum care were long labour, retained placenta, and excessive bleeding. Only a quarter of women sought care immediately after problems occurred. The main reasons seeking care late were: the woman or her family not perceiving that there was a serious problem, distance to health facility, and lack of transport. The use of skilled birth attendants at delivery among rural women in Nepal is very poor. Home delivery by unskilled birth attendants is still a common practice among them. Many associated factors relating to the use of skilled delivery care that were identified included age, education and occupation of women, and education and occupation of husbands. Therefore, the availability of skilled delivery care services at the community, initiation of a primary health centre with skilled staff for delivery, and increasing awareness among women to seek skilled delivery care are the best solution. Key words: Childbirth; Cross-sectional studies; Descriptive studies; Delivery; Rural health services; Skilled attendants; Nepal DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8453 JHPN 2011; 29(4): 371-378